PENGARUH SUKU BUNGA, KURS, INFLASI, VOLUME TRANSAKSI, DAN PELANGGAN TERHADAP HARGA SAHAM - Erna Hendriyanti Sa'adah; Setiawan, Putu Mahardika Adi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The Covid-19 pandemic has made many changes, especially in the world's economy and stock market conditions. So this study is intended to examine whether or not the influence of interest rates, exchange rates, inflation, transaction volume, and the number of customers on stock prices in operator companies in six countries with the most internet users in the world during pandemic. This research is quantitative research with a linear regression method which data collection is obtained through several pages needed in research. The collected data were then processed and tested through classical assumption tests (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test) and hypothesis testing with linear regression analysis and coefficient of determination. The test in this research uses an econometric application program, E-views version 10. The results of this research showed that the exchange rate (X2) and transaction volume (X4) have no effect on stock prices (Y), and the interest rate variable (X1) has a negative effect and significant to the stock price (Y), while the inflation variable (X3) and the number of customers partially have a positive and significant effect on stock prices (Y). Simultaneously, the variable interest rate (X1), exchange rate (X2), inflation (X3), transaction volume (X4), and the number of customers (X5) affect stock prices (Y) by 97%, while the remaining 3% is affected by other variables outside the model adopted in this research.